URDU-INTERNAL AND EXTERNAL SOURCES OF QUR'ANIC EXEGESIS; IN THE LIGHT OF THE THOUGHTS OF HAMIDUDDIN FARAHI AND AMIN AHSAN ISLAHI - Muhammad Ishfaq; Samreena Gulzaar (دی اسکالر)
Tafthir (Quranic exegesis) is a significant science that pursues the interpretation of the Quran by various means. Hamiduddin Farahi was a renowned Islamic Scholar of India, who is famous for his notion of Nazm (coherence). Amin Ahsan Islahi, an eminent Muslim Scholar of Pakistani, who wrote many books and a well-known exegesis Tadabar-ul-Quran, offered unique internal and external sources of commentary on the Quran. Islahi and Frahi presented the notion of nazm and sources of exegesis in a way that was unique from ancestors (Jamhur). Amin Ahsan Islahi gave distinctive principles of Quranic exegesis by separating internal and external sources used for commentary of the Quran. There exists a great debate over his exclusive principles of Qur’anic commentary as he refers to the discipline (Nazm) and language of the Quran as internal sources while traditions, archaeology and history as external sources. This article discusses the internal and external sources of Qur'anic exegesis in the light of Amin Ahsan Islahi's and Farahi’s thoughts.